PENENTU PRESTASI PRAKTIK INDUSTRI SISWA SMKN 3 JEPARA - Purwo Adi Wibowo; Much Imron; Mualisin Mualisin (Universitas Islam Nahdlatul Ulama Jepara, 2012)
AbstractSMK Negeri 3 Jepara in the process of learning requires their students to follow industry practice. The research purpose was to test the influence of home distance, learning achievement and motivation toward industry practice achievement. The research population was 393 students who were the XI Grade student of SMKN 3 Jepara during academic year 2009/2010. The sample was 80 students who were taken randomly. The obtained data were documented and then analyzed using multiple linear regressions. The research found that home distance was influence the industry practice achievement negatively on the contrary the learning achievement and the motivation was affect the dependent variable positively. Keywords: home residence, learning achievement, motivation, and industry practice achievement AbstrakSMK Negeri 3 Jepara dalam proses pembelajaran mewajibkan siswa untuk mengikuti praktik industri. Tujuan penelitian untuk menguji pengaruh jarak, prestasi belajar, dan motivasi terhadap prestasi praktik industri. Populasi penelitian adalah semua siswa kelas XI SMK Negeri 3 Jepara Tahun Pelajaran 2009/2010 sejumlah 393 siswa. Sampel sebanyak 80 siswa, yang diambil secara random. Data yang diperlukan dikumpulkan dengan dokumentasi, kemudian analisis data dengan regresi linier berganda. Hasil analisis menunjukkan bahwa jarak tempat tinggal berpengaruh negatif, sedangkan prestasi belajar dan motivasi berpengaruh positif. Kata Kunci: jarak tempat tinggal, prestasi belajar, motivasi, dan prestasi praktik industri